From Passive to Interactive: The Impact of Blooket Gamification to Enhance Students' Learning Motivation in Islamic Religious Education - Ahmad Abdul Hamid; Ismail Ismail; Suja’i Suja’i; M. Agung Hidayatullah; Zarkasi Zarkasi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The decline in student engagement and motivation in Islamic Religious Education (PAI) remains a significant challenge, particularly in pesantren environments where traditional teaching methods are dominant and personal gadgets are strictly prohibited. This study aims to analyze the implementation of Blooket gamification using a classical (single-screen) model as an innovative pedagogical strategy to increase students' enthusiasm for PAI learning at MA Al Wathoniyyah Semarang. Using a qualitative approach with a descriptive case study design, data were collected through intensive participant observation, in-depth interviews, and documentation from PAI teachers and 10th-grade students, then analyzed using the Miles and Huberman interactive model. The results indicate that projecting Blooket onto a main screen successfully transformed classroom dynamics from passive to highly interactive. This approach fostered a unique "collaborative competition," where students spontaneously cooperated in teams to solve quiz challenges. Theoretically, this model fulfills the ARCS motivation components (Attention, Relevance, Confidence, Satisfaction) and the relatedness aspect of Self-Determination Theory (SDT). In conclusion, classical gamification is an effective and inclusive solution to overcome infrastructure limitations. Moving forward, this model presents a promising prospect for broader adoption in similar Islamic educational institutions to integrate digital learning without violating institutional regulations.